Measuring the link between cyclical systemic risk and capital adequacy for Ukrainian banking sector - Alona Shmygel (Graduate Institute of International and Development Studies, 2023)
In this paper we investigate the impact of cyclical systemic risk on future bank profitability for a large representative panel of Ukrainian banks between 2001 and 2023. Our framework relies on two general methods. The first method is based on linear local projections which allows us to study the estimated negative impact of cyclical systemic risk on bank profitability. The second method is based on the original IMF's Growth-at-Risk approach, utilizing quantile local projections to assess the impact of cyclical systemic risk on the tails of the future bank-level profitability distribution. Additionally, we enhance the macroprudential toolkit with a novel approach to calibrating the countercyclical capital buffer (CCyB). Furthermore, we develop the "Bank Capital-at-Risk" and "Share of vulnerable banks" indicators. These indicators are valuable tools for monitoring the build-up of systemic risk in the banking sector.
Keywords: E58; G21; G32; 330; systemic risk; linear projections; quantile regressions; bank capital; macroprudential policy